Decreased piRNAs in Infertile Semen Are Related to Downregulation of Sperm MitoPLD Expression - Hong, Yeting; Wu, Yanqian; Zhang, Jianbin; Yu, Chong; Shen, Lu; Chen, Hanxiao; Chen, Linjie; Zhou, Xue; Gao, Fang (Frontiers in Endocrinology, 2021)
Currently, the molecular mechanisms underlining male infertility are still poorly understood. Our previous study has demonstrated that PIWI-interacting RNAs (piRNAs) are downregulated in seminal plasma of infertile patients and can serve as molecular biomarkers for male infertility. However, the source and mechanism for the dysregulation of piRNAs remain obscure. In this study, we found that exosomes are present in high concentrations in human seminal plasma and confirmed that piRNAs are predominantly present in the exosomal fraction of seminal plasma. Moreover, we showed that piRNAs were significantly decreased in exosomes of asthenozoospermia patients compared with normozoospermic men. By systematically screening piRNA profiles in sperms of normozoospermic men and asthenozoospermia patients, we found that piRNAs were parallelly reduced during infertility. At last, we investigated the expression of some proteins that are essential for piRNAs biogenesis in sperms and therefore identified a tight correlation between the levels of spermatozoa piRNA and MitoPLD protein, suggesting that the loss-of-function of MitoPLD could cause a severe defect of piRNA accumulation in sperms. In summary, this study identified a parallel reduction of piRNAs and MitoPLD protein in sperms of asthenozoospermia patients, which may provide pathophysiological clues about sperm motility.